2017
DOI: 10.1039/c7ra06307e
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in thermostability of an alkaline lipase I from Penicillium cyclopium by directed evolution

Abstract: A novel alkaline-stable lipase I from Penicillium cyclopium with improved thermostability was prepared by molecular modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Far-UV CD spectra in the range of 190–260 nm were recorded to determine the secondary structure of PFL. Figure 2C shows a strong positive absorption peak at 196–197 nm, which is a typical feature for α-helices, whereas a negative absorption peaks centered around 192–194 and 215–220 nm are a typical feature β-sheet structures ( Liu et al, 2017 ). The secondary structure percentages of PFL obtained from CD spectra were 18.6% α-helix, 37.9% β-sheet, 9.2% β-turn structures, and 34.6% unstructured regions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Far-UV CD spectra in the range of 190–260 nm were recorded to determine the secondary structure of PFL. Figure 2C shows a strong positive absorption peak at 196–197 nm, which is a typical feature for α-helices, whereas a negative absorption peaks centered around 192–194 and 215–220 nm are a typical feature β-sheet structures ( Liu et al, 2017 ). The secondary structure percentages of PFL obtained from CD spectra were 18.6% α-helix, 37.9% β-sheet, 9.2% β-turn structures, and 34.6% unstructured regions.…”
Section: Resultsmentioning
confidence: 99%
“…The T m values of the mutants L218P and P184C/M243C was increased from 60°C to 62.5 and 66.0°C, which was 2.5 and 6°C higher than that of the WT, respectively ( Figure 5B ). A combination of mutants with higher thermostability sometimes results in a cumulative effect ( Liu et al, 2017 ). Therefore, the combined triple mutant P184C/M243C/L218P was generated using site-directed mutagenesis using the plasmid P184C/M243C as the template.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Mohammadi et al [ 31 ] reported substitution of proline residue at position 2 in the N -terminal of lipase A from Serratia marcescens revealed a 2.3-fold higher activity at half-life of the mutant compared to the wild-type. Liu et al [ 42 ] also reported an increase of 7-fold in half-life at 45 °C of mutant alkaline lipase I from Penicillium cyclopium with proline substitution at position 41, far from the catalytic site. In both studies, the introduction of proline residue improved the stability of the structure, thus prolonging the half-life of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…For example: enantioselectivity (Engström et al 2010;K. Liebeton et al 2000a;Reetz et al 1997), stability in organic compounds (Dror et al 2014;Korman et al 2013), thermostability (Augustyniak et al 2012;Liu et al 2017;Yu et al 2012;Zhang et al 2003), substrate specificity (Fujii et al 2005).…”
Section: Sequence Analysismentioning
confidence: 99%